An explicit solution for implicit time stepping in multiplicative finite strain viscoelasticity - Shutov, A.V.; Landgraf, R.; Ihlemann, J. (Computer methods in applied mechanics and engineering, 2013)
•The popular model of the finite strain Maxwell fluid is considered.•A new explicit update formula for implicit time stepping is presented.•The algorithm is first order accurate and unconditionally stable.•Application of the algorithm to viscoelasticity is discussed.•Mathematical and numerical analysis of the algorithm is presented. We consider the numerical treatment of one of the most popular finite strain models of the viscoelastic Maxwell body. This model is based on the multiplicative decomposition of the deformation gradient, combined with Neo-Hookean hyperelastic relations between stresses and elastic strains. The evolution equation is six dimensional and describes an incompressible flow such that the volume changes are purely elastic. For the corresponding local initial value problem, a fully implicit integration procedure is considered, and a simple explicit update formula is derived. Thus, no local iterative procedure is required, which makes the numerical scheme more robust and efficient. The resulting integration algorithm is unconditionally stable and first order accurate. The incompressibility constraint of the inelastic flow is exactly preserved. A rigorous proof of the symmetry of the consistent tangent operator is provided. Moreover, some properties of the numerical solution, like invariance under the change of the reference configuration and positive energy dissipation within a time step, are discussed. Numerical tests show that, in terms of accuracy, the proposed integration algorithm is equivalent to the classical implicit scheme based on the exponential mapping. Finally, in order to check the stability of the algorithm numerically, a representative initial boundary value problem involving finite viscoelastic deformations is considered. A FEM solution of the representative problem using MSC.MARC is presented.